Research on the Spatial Effect of Igital Economy Development Enabling Green Technology Innovation in Yangtze River Delta region - Bai, Xingyu; Zheng, Zimeng (International Journal of Global Economics and Management, 2024)
At the time of the transformation of old and new driving forces for economic growth, green technology innovation enabled by the digital economy has gradually become a powerful driving force for scientific and technological innovation and the improvement of the development level of green economy in the Yangtze River Delta region. This paper takes 41 cities in the Yangtze River Delta region as the research object, and empirically analyzes the spatial correlation degree and the spillover effect of green technology innovation in the Yangtze River Delta region from 2016 to 2020 by constructing the spatial Dubin model. The results show that: (1) Digital economy has a strong positive impact on green technology innovation and development, and has an empowering effect on regional green technology innovation and development. (2) The development of green technology innovation in the Yangtze River Delta showed a significant positive spatial autocorrelation, and the spatial autocorrelation decreased with the increase of years, and the trend of unbalanced development of green technology innovation increased. (3) The level of digital economy, the level of opening up to the outside world, the rate of urbanization and the level of scientific and technological development have a spatial spillover effect on regional green technology innovation and development. Based on the above conclusions, the paper puts forward some countermeasures and suggestions to promote the innovation and development of green technology enabled by digital economy in Yangtze River Delta region.